A new species of Magnolia (Magnoliaceae) from central Peru - Arroyo, Frank (Phytotaxa, 2014)
Peruvian species of Magnolia were not included in major treatments of the Peruvian flora until the last decade, following revisions of Dugandiodendron and Talauma for the Neotropics published by Lozano-Contreras in 1994 (Pennington et al. 2004, Ulloa et al. 2004) when M. amazonica (Ducke, 1925: 11) Govaerts (1996: 25) and M. rimachii, (Lozano, 1994: 105) Govaerts (1996: 39), two lowland Amazonian species, were included. Subsequently, new species of Magnolia were described from the eastern humid montane and lowland forests in northern and central Peru (Dillon & Sanchez 2009, Vázquez-García et al. 2012). The new species reported here is described for the humid forests of the eastern Andean slopes of central Peru. Following the classification proposed by Figlar & Nooteboom (2004), this species belong to genus Magnolia subgenus Magnolia section Talauma subsection Talauma because of stipule adnation to petioles, circumscissile dehiscence of fruits and absence of a filamentous appendage in the stamen connective.